2021
DOI: 10.1177/0976399621989910
|View full text |Cite
|
Sign up to set email alerts
|

Socially Distanced or Socially Connected? Well-being through ICT Usage among the Indian Elderly during COVID-19

Abstract: The ageing of the national population along with the rapid diffusion of technological innovations necessitate it to turn our attention to the significance of considering the adoption of technology by the Indian elderly. The impact of social distancing and the role of technology on the everyday lives of the older people during the pandemic remain under-researched. The public health crisis created by COVID-19 has deepened the roots of digital divide by digitally marginalizing older people especially in the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
0
16
0
2
Order By: Relevance
“…We found that the age-related divide in Internet use remains the most important in the control of COVID-19 cases. Older people are the most vulnerable group, with limitations in using information and communication technologies and applications [7][8][9][10][11]. While digital skills are considered important for older people, we found an association only between inequality in Internet use and the incidence of COVID-19.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We found that the age-related divide in Internet use remains the most important in the control of COVID-19 cases. Older people are the most vulnerable group, with limitations in using information and communication technologies and applications [7][8][9][10][11]. While digital skills are considered important for older people, we found an association only between inequality in Internet use and the incidence of COVID-19.…”
Section: Discussionmentioning
confidence: 56%
“…The results of qualitative in-depth interviews conducted with 30 professionals of at least 60 years of age living in a metropolis in eastern India showed that when participants feel isolated, they change their traditional norms of face-to-face social interaction and rely upon their screens and keyboards to continue everyday interactions, work from home, access information, and use 'essential services'. The study highlighted the blocks to active usage of ICT, namely attitudinal barriers, prior negative experience, concerns over cyber security, complicated technical instructions, and lack of a supportive learning environment [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…3.1. Las TIC ayudaron a los adultos mayores a mantenerse conectados durante la pandemia, reduciendo los sentimientos de aislamiento social y soledad Bakshi & Bhattacharyya (2021) revelaron la naturaleza compleja del uso de las TIC para mitigar la pérdida de conexión en persona. A pesar de estar físicamente aislado de los demás, el uso de TIC por parte de algunos evitó sentimientos de aislamiento total porque las familias pudieron suavizar los impactos de las restricciones de distanciamiento social al participar en entretenimiento en línea con otros.…”
Section: Resultsunclassified
“…La pandemia de COVID-19 ha cambiado en gran medida nuestra atención hacia el uso de las tecnologías de la información y comunicación (TIC) para proteger la salud mental de los Adultos Mayores (AM) y sus Cuidadores (C). Muchos han confiado en las TIC para mantener las redes sociales y proteger el bienestar mental (Bakshi & Bhattacharyya 2021). Transculturalmente, algunos AM percibieron que las tecnologías inteligentes contribuyeron a un sentido de significado al ayudarlos a mantener relaciones sociales durante las medidas de cierre (von Humboldt et al, 2020).…”
Section: Introductionunclassified
“…Grandparents need only to send a text or audio message to communicate with their grandchildren. Even if face-to-face meetings are not available, video calls are a natural substitute (Bakshi & Bhattacharyya, 2021). Furthermore, some grandchildren invited their grandparents to use technology by posting their photos and contents on social media platforms.…”
mentioning
confidence: 99%